2016
DOI: 10.1093/ckj/sfw108
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of kinetic glomerular filtration rate

Abstract: Background: In acutely unwell patients with rapidly changing renal function, estimating glomerular filtration rate (GFR) and predicting adverse renal outcomes are challenging and often inaccurate. Kinetic GFR (kGFR) is an estimate of immediate biomarker clearance derived from two discreet measurements that may better represent acute function. Our objective is to assess the clinical utility of kGFR as a predictive tool and examine the association of kGFR to adverse renal outcomes compared with measurements to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…On the contrary, the KeGFR timeline recognises the sluggish nature of the rise in serum creatinine on the second day due to the increase rather than decrease in Cr excretion as a result of the rising GFR (as Cr generation is unlikely to change in such a short time period and assuming V D is stable). This particular aspect of KeGFR may impact the need for RRT, as already shown [9]. The authors found that KeGFR associates better with the need for RRT when compared to MDRD GFR in a retrospective series.…”
Section: Doi: 101159/000492439mentioning
confidence: 54%
See 2 more Smart Citations
“…On the contrary, the KeGFR timeline recognises the sluggish nature of the rise in serum creatinine on the second day due to the increase rather than decrease in Cr excretion as a result of the rising GFR (as Cr generation is unlikely to change in such a short time period and assuming V D is stable). This particular aspect of KeGFR may impact the need for RRT, as already shown [9]. The authors found that KeGFR associates better with the need for RRT when compared to MDRD GFR in a retrospective series.…”
Section: Doi: 101159/000492439mentioning
confidence: 54%
“…Also, the spectre of validity of baseline Cr does not loom large in these patient groups as the initial Cr is the true baseline Cr. KeGFR has been used as a prognostic tool and compared with MDRD GFR for accuracy and prediction of renal recovery [9,14].…”
Section: Doi: 101159/000492439mentioning
confidence: 99%
See 1 more Smart Citation
“…Among acute medical admissions to the high-dependency unit and intensive care unit, the AUC for AKI was 0.86 for KeGFR versus 0.64 for MDRD eGFR. The AUC for predicting the need for renal replacement therapy was 0.901 [2]. When KeGFR was used, the AUC for major adverse kidney events (MAKEs) was higher than that for novel biomarkers and Cr in another study in the intensive care unit setting from France [3].…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…The CG equation estimates Cr clearance rather than GFR and is not validated for use with IDMS-traceable Cr levels. The kinetic equation by Chen (KeGFR) estimates GFR for the nonsteady-state Cr level and is being validated in patient cohorts with acute kidney injury (AKI) [1][2][3][4][5]. In our pilot study, we were able to apply the KeGFR equation to detect AKI among acute medical admissions [6].…”
Section: Introductionmentioning
confidence: 99%